2022
DOI: 10.1155/2022/2967981
|View full text |Cite|
|
Sign up to set email alerts
|

Preventive Effect of Intensive Nursing Intervention of Deep Vein Thrombosis of Lower Extremities in Elderly Patients with Gastrointestinal Tumors after Surgery

Abstract: Tumors of the gastrointestinal system, known as gastroenteropapillary neoplasms, are very uncommon yet have a high propensity to progress to cancer. Thromboembolism of the veins (VTE) is a potentially deadly complication of surgery. In the vast majority of cases, deep vein thrombosis (DVT) in the lower extremities is the primary symptom of VTE (DVT). Deep vein thrombosis is more common in critical care units, where the prevalence ranges from 18 to 50 percent. DVT is a common complication after gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, chronic joint pain can incur high medical costs that impose a heavy financial burden on patients 10 . Patients with arthritis would suffer from decreased activities of daily life, more negative emotions, and higher overall care support needs after experiencing longterm illness 11 . Therefore, scientific and effective management of pain in arthritis is essential to relieve the pain, reduce the disease burden, and improve the quality of life [12][13][14] .…”
mentioning
confidence: 99%
“…In addition, chronic joint pain can incur high medical costs that impose a heavy financial burden on patients 10 . Patients with arthritis would suffer from decreased activities of daily life, more negative emotions, and higher overall care support needs after experiencing longterm illness 11 . Therefore, scientific and effective management of pain in arthritis is essential to relieve the pain, reduce the disease burden, and improve the quality of life [12][13][14] .…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%